The Efforts of Al-Khalil bin Ahmad Al-Farahidi and His Views on the Science of Dots through the Book The Decisiveness of Punctuation in Quran by Abi Amr Al-Dani: Exploration and Analysis (Islamic Sciences Journal, 2023)
ABSTRACT              This research discusses the efforts of Al-Khalil bin Ahmed Al-Farahidi and his opinions on the science of punctuation through the book The Decisiveness of punctuation in the Qur’an” by Abi Amr by al-Dani. The research discusses the development of punctuation, the stages it went through, its types, its causes, and the critical perspectives of scholars in its provisions.  The research is concluded with the terms related to punctuation.
Keywords: punctuation, Khalil, The Decisiveness of Punctuation in Quran, al-Dani, efforts.